A Continuous-Time Distributed Algorithm for Solving a Class of Decomposable Nonconvex Quadratic Programming - Zhao, Yan; Liu, Qingshan (Journal of Artificial Intelligence and Soft Computing Research, 2018)
In this paper, a continuous-time distributed algorithm is presented to solve a class of decomposable quadratic programming problems. In the quadratic programming, even if the objective function is nonconvex, the algorithm can still perform well under an extra condition combining with the objective, constraint and coupling matrices. Inspired by recent advances in distributed optimization, the proposed continuous-time algorithm described by multi-agent network with consensus is designed and analyzed. In the network, each agent only accesses the local information of its own and from its neighbors, then all the agents in a connected network cooperatively find the optimal solution with consensus.